2004
DOI: 10.1002/cncr.20506
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve follow-up of abnormal findings in cancer screening

Abstract: The potential reduction in morbidity and mortality through cancer screening cannot be realized without receipt of appropriate follow-up care for abnormalities identified via screening. In this paper, the authors critically examine the existing literature on correlates of receipt of appropriate follow-up care for screen-detected abnormalities, as well as the literature on interventions designed to increase rates of receipt of follow-up care. Lessons learned describe what is known and not known about factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
98
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 86 publications
1
98
0
Order By: Relevance
“…These include telephone and mailed reminders and educational interventions to address fear of cancer diagnosis (19). Myers et al (20) showed that a physician-based intervention of reminderfeedback and educational outreach improved the evaluation of positive FOBT.…”
Section: Discussionmentioning
confidence: 99%
“…These include telephone and mailed reminders and educational interventions to address fear of cancer diagnosis (19). Myers et al (20) showed that a physician-based intervention of reminderfeedback and educational outreach improved the evaluation of positive FOBT.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to obtain appropriate diagnostic services can have a significant negative effect on health outcomes, as well as costs for both the individual and the healthcare system. 1 A systematic review of follow-up care after abnormal screening tests for cervical, breast, and colon cancer showed that < 75% of women received timely and appropriate follow-up care. 2 The proportion of women who were followed after abnormal Pap tests varies dramatically across studies, ranging from 7% to 73%.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete or delayed diagnostic resolution can result in larger tumors, locally advanced or metastatic cancer, costlier treatment options (1), higher recurrence rates (2,3), and lower 5-year survival rates (4)(5)(6)(7). However, little research has focused on improving timely resolution of abnormal findings (8). This is troublesome given that only about 75% of all patients in the general population and 50% to 70% of minority women who test positive on any screening test receive appropriate follow-up care (9,10).…”
Section: Introductionmentioning
confidence: 99%